Mind the gap: comparison of external load and load variation between a reserve team in a 1-game week microcycle and its first team in a 2-game week microcycle within an elite professional soccer club - Carpels, T.; Scobie, N.; Macfarlane, N. G.; Kemi, O. J. (The Journal of Strength and Conditioning Research, 2024)
The aim of this study was to quantify and compare weekly external load and within-week load variation of reserve team players (RES) in a 1-game week microcycle to first team players (FT) in a 2-game week microcycle within the same professional soccer club. External load data were collected between 2017 and 2020 for the following parameters: duration, total distance (TD), total high-speed distance (THSD; >19.8 km·h-1), high-speed distance (HSD; 19.8-25.2 km·h-1), sprint distance (SD; >25.2 km·h-1), number of sprints (number of efforts >25.2 km·h-1), number of high-speed efforts (number of HS efforts >19.8 km·h-1), meters per minute (m·min-1), and high-speed meters per minute (HS m·min-1). First team players were subcategorized into starters (ST) and nonstarters (NST). Intergroup differences in cumulative weekly load and weekly load patterns were statistically analyzed, whereas training monotony (TM) was quantified to assess intragroup, within-week, load variation. Reserve team players showed similar weekly loads to ST, apart from significant differences (p < 0.005) in duration (8%), TD (21%), and HS efforts (16%). Similar to ST, RES showed greater values than NST (p < 0.0005) for duration (10%), TD (9%), THSD (30%), HSD (26%), SD (45%), sprints (40%), and HS efforts (22%). Weekly patterns in RES were different from ST and NST (p < 0.05). Training monotony was highest for NST for all parameters, apart from the number of sprints. Reserve team players need to be prepared to cope with cumulative weekly loads and the lack of recovery between games that ST face. However, when RES become NST, effective loading strategies need to be designed within the limits of 2-game week microcycles to ensure continuous development.